Relationship between the prevalence of trachomatous inflammation in children (age 1-9years) and the prevalence of trichiasis in adults (age 15years and above) at a presumed steady state - Antwi-Adjei, Ellen K (Department of Public Law, 2017)
Background: Trachoma is the leading cause of infectious eye disease that leads to blindness. Continuous re-infection by the bacteria, Chlamydia trachomatis, leads to scarring of the cornea and subsequently to blindness. It is commonly found in the poorest and remotest part of Africa, Asia, Latin America and Mid-east, where hygienic conditions are also poorer. The Alliance for the Global Elimination of Blinding Trachoma by the year 2020 (GET 2020) was launched by World Health Organization (WHO) with the main aim of eliminating trachoma as a public health problem globally by year 2020. The Alliance funded Sightsavers, as part of the strategy to meet this target, to set up the Global Trachoma Mapping Project (GTMP) which was to map all endemic places for intervention through a population-based prevalence survey. There are five main signs of the disease and the number of people affected by each sign explains the magnitude and the intervention needed in that population. WHO recommends the active trachoma survey in children age 1-9 years and the blinding signs in adults' age 15 years and above. More researches, that establish quicker means of intervention for the endemic trachoma areas, are needed using the GTMP data in order to meet the year 2020 target. Methods: Baseline data from the Global Trachoma Mapping Project (GTMP) was used as a secondary dataset for this research. All eligible regions in Ethiopia were included. The GTMP teams conducted surveys in seven regions. All age groups were included, but for the purpose of planning, the study assessed TF in children age 1-9 years and TT in adults age 15 years and above. The prevalence of TF in children and TT in adults are indicators for programme decision making for intervention and establishing the relationship between them would aid in the intervention. The relationship if established could help in planning the extent of intervention needed in a given population. Data on sanitation and hygiene as well as altitude, which were collected as part of GTMP, were assessed to determine if they contributed to relationship between TF and TT. Results: The study included a total of 282,558 individuals living in 174 evaluation units from seven regions of Ethiopia, among whom 256,587 gave consent to be examined. This study found a significant relationship between the prevalence of TF in children and the prevalence of TT in adults when analysis is done at the evaluation unit level (correlation rho, 0.59; p-value <0.0001). Hence, 59% of the prevalence of TT in adults can be explained for by the presence of TF in children. Sub-group analysis showed that the correlation persisted at the regional level. Conclusion: A better understanding of the relationship between the prevalence of TF and the prevalence of TT together with the factors influencing this association using this large dataset may aid in prioritization of districts for intervention and has implications for global activities for the elimination of trachoma.